Keberlanjutan Agribisnis Vanili di Kabupaten Sumedang, Jawa Barat - Setiawan, Darma; Setiawan, Iwan; Wulandari, Eliana (Analisis Kebijakan Pertanian, 2025)
The quality of vanilla grown in Indonesia is known for its substantially high vanilla content (2.75%) compared to products from Madagascar (2.2%), Sri Lanka (1.5%), and Mexico (1.75%). However, vanilla agribusiness in Indonesia is still not sustainable. This study aims to analyze the index and status of vanilla agribusiness sustainability and identify attributes that are sensitive to the sustainability of vanilla agribusiness. The analytical method used was Multidimensional Scaling (MDS). Data was collected through interviews with structured questionnaires from November to December 2022 in Sumedang Regency, West Java Province. The selection of 67 farmers to be interviewed used proportional stratified random sampling. The results showed the sustainability index on the economic (55.22%), social (52.84%), environmental (52.46%), technological (57.81%), and institutional (55.22%) dimensions so that vanilla agribusiness can be categorized as sufficiently sustainable. The variables that are sensitive to sustainability are 1) prices and income from the economic dimension; 2) farmer empowerment, farmer regeneration, and group dynamics from the social dimension; 3) farmers' awareness of the environment, adaptation and mitigation of climate change, and water use efficiency from the environmental dimension; 4) technological innovation, productivity and production risk control from the technological dimension; 5) support and the role of government and socio-cultural support from the institutional dimension. Recommendations from the results of this study, among others, are the need to transform vanilla products into highly competitive ones, empower farmers to adopt technological innovations in vanilla cultivation and processing and increase farmer awareness of the importance of environmental sustainability.
Keywords: agribusiness sustainability; multidimensional scaling (MDS); vanilla agribisiness